Directions in empirical literary studies : in honor of Willie van Peer - Peer, Willie van; Zyngier, Sonia (Linguistic approaches to literature ;, 2008)
Directions in Empirical Literary Studies is on the cutting edge of empirical studies and is a much needed volume. It both widens the scope of empirical studies and looks at them from an intercultural perspective by bringing together renowned scholars from the fields of philosophy, sociology, psychology, linguistics and literature, all focusing on how empirical studies have impacted these different areas. Theoretical issues are discussed and solid methods are presented. Some chapters also show the relation between empirical studies and new technology, examining developments in computer science.